2003
DOI: 10.1111/j.1751-0813.2003.tb12886.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that enforced sunlight exposure can cause hyperthermia in cattle ingesting low levels of ergot of rye (Claviceps purpurea), when air temperature and humidity conditions are only moderate

Abstract: Some sunlight exposed cattle, dosed with a low amount of ergot of rye, can experience a body temperature elevation above the normal range, even under mild ambient temperature and humidity conditions. Sunlight exposure causes an increase in body temperature in normal cattle that is probably attributable to solar radiant heat. Ergot ingestion causes an increase in body temperature in shaded cattle that is probably attributable to ambient temperature and humidity effects. This response can be increased by sun exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
14
1
1
Order By: Relevance
“…Bourke (2003) found that solar radiation made an important contribution to hyperthermia in cattle that ingested ergot when air temperatures were relatively low and this is likely also the case for cattle with dark coats. Blackshaw and Blackshaw (1994) state that shade can reduce an animal's radiant heat load by 30%.…”
Section: Provision Of Shadementioning
confidence: 94%
“…Bourke (2003) found that solar radiation made an important contribution to hyperthermia in cattle that ingested ergot when air temperatures were relatively low and this is likely also the case for cattle with dark coats. Blackshaw and Blackshaw (1994) state that shade can reduce an animal's radiant heat load by 30%.…”
Section: Provision Of Shadementioning
confidence: 94%
“…The impact of ergot is more serious in lot-fed conditions, and serious mortalities occurred in several Western Australian feedlots in 1990 from feeding barley containing 0.06% rye grass ergot (Peet et al 1991). Bourke (2000) reviewed more cases in central NSW in 1998 and 1999. Here we report further cases from central NSW and South Australia in 2001 and 2002, involving some mortalities.…”
Section: Cases Of Ergotismmentioning
confidence: 99%
“…Poisoning of livestock occurs only occasionally and in a few localities, usually as a result of grazing infected rye grass (Jessep et al 1987). However, it also occurs from feeding contaminated grain to livestock, if rye grass is not controlled in winter cereal crops, which are then contaminated by ergot sclerotia produced in the rye grass (Peet et al 1991;Bourke 2000). Rye grass ergot sclerotia in grain traded by bulk handlers are limited by industry trading standards and some state government regulations, but toxicity problems can result from direct sales from farm to farm.…”
Section: Introductionmentioning
confidence: 99%
“…However, he concluded that stock exposure to sunlight appears to be a critical factor in a particularly lethal form of hyperthermia in cattle and sheep and that toxins other than ergot alkaloids could be involved such as the ergochromes (Franck 1969;Buchta and Cvak 1999). Bourke (2003) suggested that feed likely to contain rye ergot should be avoided for ruminant feed, particularly in feedlot rations. For practical purposes it is preferred to propose a low level rather than a zero tolerance and a level of 0.01% ergot sclerotia in the total diet of cattle, goats and sheep is proposed, with an equivalent alkaloid content limit of 0.2 mg/kg.…”
Section: Ergot Alkaloidsmentioning
confidence: 99%